The 5th generation regional climate modeling system, RegCM5: the first convection-permitting European wide simulation and validation over the CORDEX-CORE domains - Erika Coppola; Filippo Giorgi; Graziano Giuliani; Emanuela Pichelli; James M. Ciarlo; Francesca Raffaele; Rita Nogherotto; Michelle Simões Reboita; Chen Lu; Natalia Zazulie; Luiza Vargas-Heinz; Andressa Andrade Cardoso; et al. (Climate Dynamics, 2025)

Evaluation of the near-surface wind field over the Adriatic region: local wind characteristics in the convection-permitting model ensemble - Andreina Belušić Vozila; Danijel Belušić; Maja Telišman Prtenjak; Ivan Güttler; Sophie Bastin; Erwan Brisson; Marie-Estelle Demory; Andreas Dobler; Hendrik Feldmann; Øivind Hodnebrog; Stergios Kartsios; Klaus Keuler; et al. (Climate Dynamics, 2024)

The added value of km-scale simulations to describe temperature over complex orography: the CORDEX FPS-Convection multi-model ensemble runs over the Alps - P. M. M. Soares; J. A. M. Careto; Rita M. Cardoso; Klaus Goergen; Eleni Katragkou; Stefan Sobolowski; Erika Coppola; Nikolina Ban; Danijel Belušić; Ségolène Berthou; Cécile Caillaud; Andreas Dobler; et al. (Climate Dynamics, 2024)
The increase in computational resources has enabled the emergence of multi-model ensembles of convection-permitting regional climate model (CPRCM) simulations at very high horizontal resolutions. An example is the CORDEX Flagship Pilot Study on “Convective phenomena at high resolution over Europe and the Mediterranean”, a set of kilometre-scale simulations over an extended Alpine domain. This first-of-its-kind multi-model ensemble, forced by the ERA-Interim reanalysis, can be considered a benchmark dataset. This study uses a recently proposed metric to determine the added value of all the available Flagship Pilot Study hindcast kilometre-scale simulations for maximum and minimum temperature. The analysis is performed using state-of-the-art gridded and station observations as ground truth. This approach directly assesses the added value between the high-resolution CPRCMs against their driving global simulations and coarser resolution RCM counterparts. Overall, models display some modest gains, but also considerable shortcomings are exhibited. In part, these deficiencies can be attributed to the assimilation of temperature observations into ERA-Interim. Although the gains for the use of kilometre-scale resolution for temperature are limited, the improvement of the spatial representation of local atmospheric circulations and land–atmosphere interactions can ultimately lead to gains, particularly in coastal areas.

The climate change response of alpine-mediterranean heavy precipitation events - Sebastian K. Müller; Emanuela Pichelli; Erika Coppola; Segolene Berthou; Susanne Brienen; Cécile Caillaud; Marie-Estelle Demory; Andreas Dobler; Hendrik Feldmann; Paola Mercogliano; Merja Tölle; Hylke de Vries (Climate Dynamics, 2024)

Correction to: Evaluation of Alpine-Mediterranean precipitation events in convection-permitting regional climate models using a set of tracking algorithms - Sebastian K. Müller; Cécile Caillaud; Steven Chan; Hylke de Vries; Sophie Bastin; Ségolène Berthou; Erwan Brisson; Marie-Estelle Demory; Hendrik Feldmann; Klaus Goergen; Stergios Kartsios; Petter Lind; et al. (Climate Dynamics, 2023)

Evaluation of Alpine-Mediterranean precipitation events in convection-permitting regional climate models using a set of tracking algorithms - Sebastian K. Müller; Cécile Caillaud; Steven Chan; Hylke de Vries; Sophie Bastin; Ségolène Berthou; Erwan Brisson; Marie-Estelle Demory; Hendrik Feldmann; Klaus Goergen; Stergios Kartsios; Petter Lind; et al. (Climate Dynamics, 2023)

Climate hazard indices projections based on CORDEX-CORE, CMIP5 and CMIP6 ensemble - Erika Coppola; Francesca Raffaele; Filippo Giorgi; Graziano Giuliani; Gao Xuejie; James M. Ciarlo; Taleena Rae Sines; José Abraham Torres-Alavez; Sushant Das; Fabio di Sante; Emanuela Pichelli; Russell Glazer; et al. (Climate Dynamics, 2021)

Assessing mean climate change signals in the global CORDEX-CORE ensemble - Claas Teichmann; Daniela Jacob; Armelle Reca Remedio; Thomas Remke; Lars Buntemeyer; Peter Hoffmann; Arne Kriegsmann; Ludwig Lierhammer; Katharina Bülow; Torsten Weber; Kevin Sieck; Diana Rechid; et al. (Climate Dynamics, 2021)
The new Coordinated Output for Regional Evaluations (CORDEX-CORE) ensemble provides high-resolution, consistent regional climate change projections for the major inhabited areas of the world. It serves as a solid scientific basis for further research related to vulnerability, impact, adaptation and climate services in addition to existing CORDEX simulations. The aim of this study is to investigate and document the climate change information provided by the CORDEX-CORE simulation ensemble, as a part of the World Climate Research Programme (WCRP) CORDEX community. An overview of the annual and monthly mean climate change information in selected regions in different CORDEX domains is presented for temperature and precipitation, providing the foundation for detailed follow-up studies and applications. Initially, two regional climate models (RCMs), REMO and RegCM were used to downscale global climate model output. The driving simulations by AR5 global climate models (AR5-GCMs) were selected to cover the spread of high, medium, and low equilibrium climate sensitivity at a global scale. The CORDEX-CORE ensemble has doubled the spatial resolution compared to the previously existing CORDEX simulations in most of the regions (25 $$\,km$$ km (0.22 $$^{° }$$ ∘ ) versus 50 $$\,km$$ km (0.44 $$^{° }$$ ∘ )) leading to a potentially improved representation of, e.g., physical processes in the RCMs. The analysis focuses on changes in the IPCC physical climate reference regions. The results show a general reasonable representation of the spread of the temperature and precipitation climate change signals of the AR5-GCMs by the CORDEX-CORE simulations in the investigated regions in all CORDEX domains by mostly covering the AR5 interquartile range of climate change signals. The simulated CORDEX-CORE monthly climate change signals mostly follow the AR5-GCMs, although for specific regions they show a different change in the course of the year compared to the AR5-GCMs, especially for RCP8.5, which needs to be investigated further in region specific process studies.

A new spatially distributed added value index for regional climate models: the EURO-CORDEX and the CORDEX-CORE highest resolution ensembles - James M. Ciarlo`; Erika Coppola; Adriano Fantini; Filippo Giorgi; XueJie Gao; Yao Tong; Russell H. Glazer; Jose Abraham Torres Alavez; Taleena Sines; Emanuela Pichelli; Francesca Raffaele; Sushant Das; et al. (Climate Dynamics, 2021)

The first multi-model ensemble of regional climate simulations at kilometer-scale resolution, part I: evaluation of precipitation - Nikolina Ban; Cécile Caillaud; Erika Coppola; Emanuela Pichelli; Stefan Sobolowski; Marianna Adinolfi; Bodo Ahrens; Antoinette Alias; Ivonne Anders; Sophie Bastin; Danijel Belušić; Ségolène Berthou; et al. (Climate Dynamics, 2021)
Here we present the first multi-model ensemble of regional climate simulations at kilometer-scale horizontal grid spacing over a decade long period. A total of 23 simulations run with a horizontal grid spacing of $$\sim $$ ∼ 3 km, driven by ERA-Interim reanalysis, and performed by 22 European research groups are analysed. Six different regional climate models (RCMs) are represented in the ensemble. The simulations are compared against available high-resolution precipitation observations and coarse resolution ( $$\sim $$ ∼ 12 km) RCMs with parameterized convection. The model simulations and observations are compared with respect to mean precipitation, precipitation intensity and frequency, and heavy precipitation on daily and hourly timescales in different seasons. The results show that kilometer-scale models produce a more realistic representation of precipitation than the coarse resolution RCMs. The most significant improvements are found for heavy precipitation and precipitation frequency on both daily and hourly time scales in the summer season. In general, kilometer-scale models tend to produce more intense precipitation and reduced wet-hour frequency compared to coarse resolution models. On average, the multi-model mean shows a reduction of bias from $$\sim \,$$ ∼ −40% at 12 km to $$\sim \,$$ ∼ −3% at 3 km for heavy hourly precipitation in summer. Furthermore, the uncertainty ranges i.e. the variability between the models for wet hour frequency is reduced by half with the use of kilometer-scale models. Although differences between the model simulations at the kilometer-scale and observations still exist, it is evident that these simulations are superior to the coarse-resolution RCM simulations in the representing precipitation in the present-day climate, and thus offer a promising way forward for investigations of climate and climate change at local to regional scales.

The first multi-model ensemble of regional climate simulations at kilometer-scale resolution part 2: historical and future simulations of precipitation - Emanuela Pichelli; Erika Coppola; Stefan Sobolowski; Nikolina Ban; Filippo Giorgi; Paolo Stocchi; Antoinette Alias; Danijel Belušić; Segolene Berthou; Cecile Caillaud; Rita M. Cardoso; Steven Chan; et al. (Climate Dynamics, 2021)

Regional climate downscaling over Europe: perspectives from the EURO-CORDEX community - Daniela Jacob; Claas Teichmann; Stefan Sobolowski; Eleni Katragkou; Ivonne Anders; Michal Belda; Rasmus Benestad; Fredrik Boberg; Erasmo Buonomo; Rita M. Cardoso; Ana Casanueva; Ole B. Christensen; et al. (Regional Environmental Change, 2020)
The European CORDEX (EURO-CORDEX) initiative is a large voluntary effort that seeks to advance regional climate and Earth system science in Europe. As part of the World Climate Research Programme (WCRP) - Coordinated Regional Downscaling Experiment (CORDEX), it shares the broader goals of providing a model evaluation and climate projection framework and improving communication with both the General Circulation Model (GCM) and climate data user communities. EURO-CORDEX oversees the design and coordination of ongoing ensembles of regional climate projections of unprecedented size and resolution (0.11° EUR-11 and 0.44° EUR-44 domains). Additionally, the inclusion of empirical-statistical downscaling allows investigation of much larger multi-model ensembles. These complementary approaches provide a foundation for scientific studies within the climate research community and others. The value of the EURO-CORDEX ensemble is shown via numerous peer-reviewed studies and its use in the development of climate services. Evaluations of the EUR-44 and EUR-11 ensembles also show the benefits of higher resolution. However, significant challenges remain. To further advance scientific understanding, two flagship pilot studies (FPS) were initiated. The first investigates local-regional phenomena at convection-permitting scales over central Europe and the Mediterranean in collaboration with the Med-CORDEX community. The second investigates the impacts of land cover changes on European climate across spatial and temporal scales. Over the coming years, the EURO-CORDEX community looks forward to closer collaboration with other communities, new advances, supporting international initiatives such as the IPCC reports, and continuing to provide the basis for research on regional climate impacts and adaptation in Europe.